The Effect of Body Mass Index and Metformin on Matrix Gene Expression in Arthritic Primary Human Chondrocytes. (December 2021) - Schadler, Paul; Lohberger, Birgit; Stündl, Nicole; Stradner, Martin Helmut; Glänzer, Dietmar; Sadoghi, Patrick; Leithner, Andreas; Steinecker-Frohnwieser, Bibiane
Objective: Obesity is a known risk factor for knee osteoarthritis (OA). Diabetes has been associated with progression of OA and metformin is the first-line treatment in type 2 diabetes. The effect of the body mass index (BMI) and metformin on the expression of certain matrix genes in human chondrocytes is unclear. The purpose of this study was to investigate the effect of BMI and metformin on the expression of matrix genes in primary human chondrocytes. Design: Adult female patients undergoing knee arthroplasty for end-stage OA were enrolled. Primary chondrocytes were cultivated and stimulated with metformin. Matrix gene expression was analyzed using polymerase chain reaction. Clinical data were used in multivariable regression models to assess the influence of BMI and metformin stimulation on gene expression. Results: A total of 14 patients were analyzed. BMI was a predictor of increased expression in ADAMTS5 (β = −0.11, P = 0.03). Metformin slightly reduced expression in ADAMTS5 (β = 0.34, P = 0.04), HIF-1a (β = 0.39, P = 0.04), IL4 (β = 0.30, P = 0.02), MMP1 (β = 0.47, P < 0.01), and SOX9 (β = 0.37, P = 0.03). The hip-knee-ankle angle and proton pump inhibitors (PPIs) intake were associated with reduced SOX9 expression (β = 0.23, P < 0.01; β = 2.39, P < 0.01). Higher C-reactive protein (CRP) levels were associated with increased MMP1 expression (β = −0.16, P = 0.02). Conclusion: We found that BMI exerts a destructive effect via induction of ADAMTS5. Metformin reduced the expression of catabolic genes ADAMTS5 and MMP1 and might play a role in disease prevention. Limb malalignment and PPI intake was associated with a reduced expression of SOX9, and higher CRP levels correlated with increased MMP1 expression, indicating a destructive process.